2016
DOI: 10.1590/0100-69912016001005
|View full text |Cite
|
Sign up to set email alerts
|

Use of raw Euphorbia tirucalli extract for inhibition of ascitic Ehrlich tumor

Abstract: Treatment with ETHE after inoculation of Ehrlich Tumor decreases its development and increases survival and the bone marrow cellularity, thus reducing the myelosuppression present in the Ehrlich Tumor bearing mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
1
7
0
1
Order By: Relevance
“…It has also been shown that autophagic structures are present in gliomas in vivo after treatments [38]. Moreover, our results agree with other studies, which have used TMZ, arsenic trioxide and berberine (natural compound) to induce autophagic cell death in malignant glioma cells, and shown that Baf enhanced the effect of TMZ and arsenic trioxide, by inducing apoptosis [39,40]. In summary, these results suggest that autophagy plays a crucial role in the antiproliferative mechanism of euphol against glioma cells, and that inhibiting autophagy will improve the effectiveness of treatment.…”
Section: Discussionsupporting
confidence: 92%
“…It has also been shown that autophagic structures are present in gliomas in vivo after treatments [38]. Moreover, our results agree with other studies, which have used TMZ, arsenic trioxide and berberine (natural compound) to induce autophagic cell death in malignant glioma cells, and shown that Baf enhanced the effect of TMZ and arsenic trioxide, by inducing apoptosis [39,40]. In summary, these results suggest that autophagy plays a crucial role in the antiproliferative mechanism of euphol against glioma cells, and that inhibiting autophagy will improve the effectiveness of treatment.…”
Section: Discussionsupporting
confidence: 92%
“…Meroterpenoids Ehrlich's tumor exhibits strong inflammatory phenomena, including edema and inflammatory infiltrates, which are believed to play an essential role in tumor growth in various types of cancer [42,43,44,45,46]. But the anti-inflammatory effects were reported by meroterpenoids [47] and were observed in this research showing that the extract reduces inflammation, reducing the tumor by an indirect route.…”
Section: P Purpurogenum Extract Showed Activity Against Ehrlich's Somentioning
confidence: 60%
“…These results indicated that euphol is an active ingredient of E. tirucalli that exerts anticancer effects, possibly by arresting cell cycle progression of cancer cells. Santos et al (13) also demonstrated that E. tirucalli extract inhibited the growth of Ehrlich ascites tumor. Furthermore, euphol inhibited the growth of human gastric cancer cells by modulating apoptosis mediated by ERK1/2 and cyclin D1 (7).…”
Section: Introductionmentioning
confidence: 94%
“…Recently, Palharini et al (12) investigated eutirucallin, a lectin with antitumor and antimicrobial properties. Some of these active components have been reported to have biological activities, such as preventive anticancer activity, antitumor, antimutagenic, antibacterial, laxative, antiseptic, disinfectant, anti-inflammatory, antistreptococcal, antiparasitic, antiulcer, analgesic, antiasthmatic and expectorant properties, as well as anticancer effects against specific types of cancer of the breast, lung, cervix, esophagus and mouth (13).…”
Section: Introductionmentioning
confidence: 99%